The assessment of the fibrinogen-to-platelet ratio for predicting mortality of COVID-19 in non-diabetic subjects. - Reyes-Ruiz, José Manuel; Ríos-Ríos, Monserratte; Martínez-Mier, Gustavo (International Journal of Environmental Health Research, 2026)
Little is known about the biomarkers of mortality in SARS-CoV-2-infected patients without a previous diagnosis of diabetes. Thus, this study aimed to assess the fibrinogen-to-platelet ratio (FPR) and compare its predictive value with the main biomarkers for COVID-19 mortality, such as neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), leukocyte glucose index (LGI), and lactate dehydrogenase (LDH)/lymphocyte ratio. This retrospective cohort study in a population of Mexico included 70 non-diabetic patients with COVID-19 from 1 May 2020 to 30 September 2020. Non-survivors (n = 25) had higher leukocytes (p = 0.004), neutrophils (p = 0.003), FPR (p < 0.0001), and NLR (p = 0.006) values in comparison with survivors (n = 45). Area Under the Curve (AUC) of FPR (AUC = 0.71) was higher than for NLR (AUC = 0.69). Cox regression analysis revealed that FPR > 34.2 (Hazard Ratio (HR) = 2.05, 95% confidence interval (CI) 1.39–3.03, Pcorrected = 0.0009) was an independent predictor for COVID-19 mortality. Our findings suggest that FPR levels on admission greater than 34.2 could effectively predict the mortality of SARS-CoV-2-infected patients without a previous diagnosis of diabetes. In contrast, the main known biomarkers of COVID-19 mortality, such as NLR, PLR, LGI, PAFI ratio, and LDH/lymphocyte ratio, were irrelevant in this study.